Open Water Characteristics and Free Vibration Analysis of Actual and Scaled Marine Propeller - D. Harsha Vardhan, Dr. A. Ramesh, Dr. B. Chandra Mohan Reddy (International Journal of Advanced Science and Technology, 2020)
The performance characteristics of a marine propeller depend on the deviation of its torque, thrust, and efficiency with its advancing speed and revolution rate in open water. To evaluate open water characteristics of DTNRSC 4381 Propeller, the advance velocity of the propeller varied from 0.4 to 1.1 in step size of 0.1 and keeping remaining parameters fixed. Propeller design input parameters are as per the twin-screw passenger ferry. Propeller is scaled as per the law of similarity. OpenProp is the coding tool used with MATLAB for analyzing open water characteristics and to develop 2D section curves of the propeller. Propeller then modeled in SolidWorks, meshed in Hypermesh, then free vibration analysis carried in ANSYS workbench. Propeller scaled down as the law of similarity. The results showed that the open water characteristics of the actual and scaled propeller are very close together for torque, thrust coefficients, and efficiencies. Free vibration results of the actual and scaled model proved that the increase in the natural frequency of the propeller equitant to the time of geometric similarity index. The mode shapes of the actual and scaled propeller are the same.  The performance characteristics of a marine propeller depend on the deviation of its torque, thrust, and efficiency with its advancing speed and revolution rate in open water. To evaluate open water characteristics of DTNRSC 4381 Propeller, the advance velocity of the propeller varied from 0.4 to 1.1 in step size of 0.1 and keeping remaining parameters fixed. Propeller design input parameters are as per the twin-screw passenger ferry. Propeller is scaled as per the law of similarity. OpenProp is the coding tool used with MATLAB for analyzing open water characteristics and to develop 2D section curves of the propeller. Propeller then modeled in SolidWorks, meshed in Hypermesh, then free vibration analysis carried in ANSYS workbench. Propeller scaled down as the law of similarity. The results showed that the open water characteristics of the actual and scaled propeller are very close together for torque, thrust coefficients, and efficiencies. Free vibration results of the actual and scaled model proved that the increase in the natural frequency of the propeller equitant to the time of geometric similarity index. The mode shapes of the actual and scaled propeller are the same.